High serum laminin and type IV collagen levels in schistosomiasis mansoni - Wyszomirska,Rozangela Maria de Almeida Fernandes (2005)
BACKGROUND: Fibrosis is the process of excessive deposition of collagen and other extra cellular matrix components and large amounts of these components have been shown in periovular schistosomal granulomas, especially in the liver. Laminin and type IV collagen have been investigated in various hepatic disorders but their accuracy in fibrosis detection and in the evaluation of its progression in schistosomiasis have not been fully explained. AIM: To measure the serum levels of two markers of fibrosis, laminin and type IV collagen in schistosomiasis. PATIENTS AND METHODS: Sixty-four patients with different clinical forms of schistosomiasis mansoni: intestinal (group I), hepatointestinal (group II), compensated (group III) and decompensated hepatosplenic (group IV) and 18 healthy volunteers were included. RESULTS: Serum type IV collagen and laminin levels were significantly increased in patients compared to controls. At about clinical forms, serum type IV collagen was increased in groups II and IV, compared to controls and was significantly higher in group IV than in group I. Serum laminin was significantly increased in groups II, III and IV and was significantly higher in group IV than in group II. Serum type IV collagen was closely correlated with serum laminin in groups II and IV. CONCLUSIONS: Connective tissue marker levels did not correlate with periportal thickness. In schistosomiasis mansoni there is an increase of type IV collagen and laminin levels at the initial stage of the disease, as well as in advanced forms. We also suggest that these markers may be a useful predictor of disease progression.